Building a Minimum Viable Brand – Best Practice for Startups - Simon Walter; Florian Heinemann; Philipp Haberstock; Torben Wiesmann (Marketing Review St.Gallen, 2023)
Based on a joint research project by venture capital investor Project A and the International School of Management, this article discusses the concept of the minimum viable brand and proposes a corresponding framework for early-stage ventures.
Keywords: 650